Pengambilan Keputusan mengenai Pengobatan pada Pasien Kanker Payudara yang Menjalani Pengobatan Tradisional - Arina Shabrina; Aulia Iskandarsyah (Jurnal Psikologi, 2019)
There were breast cancer patients who undergo traditional treatment. The aim of this study was to describe the contributing factors in traditional treatment decision making. Five breast cancer patients were recruited from an online survey, cancer community and traditional treatment clinic. Respondents filled the demographic and clinical characteristic form and also interviewed. Thematic analysis was used to analyze the data. The result of this study was most of the respondents put more trust in traditional treatment therapist rather than a doctor. Most of them undergo a traditional treatment because they perceived the benefits of the treatment. A family member suggested they undergo traditional treatment. There were several factors that contributed to participant’s decision to undergo a traditional treatment; ie (1) the view about health care provider, (2) the perceived benefit from the treatment and (3) the source of recommendation about the use of traditional treatment.